A pilot study on effectiveness of oral mucositis pain control in hematopoietic stem cell transplant patients - Shu Ping Wong, Farida Islahudin (Journal of Applied Pharmaceutical Science, 2019)
Effectiveness of oral mucositis (OM) pain control with the current standard of care management was assessed using clinician and self-reported scales in hematopoietic stem cell transplant (HSCT) patients. A prospective observational study was performed using clinician-assessed [World Health Organization (WHO)] Oral Toxicity Scales and self-reported scales [Oral Mucositis Daily Questionnaires (OMDQ)]. A total of 23 HSCT patients were included in the study. There were 100 recorded days of OM using WHO scores, and 144 recorded days of OM using OMDQ. A total of 14/23 (60.9%) patients experienced mucositis. The presence of OM was significantly associated with increase in actual body weight [t(21) = 2.15, p = 0.044], body surface area (BSA) [t(21) = 2.31, p = 0.031] and body mass index (BMI) [t(21) = 2.13, p = 0.044], longer hospital stays [t(21) = 2.45, p = 0.023], and busulphan-based regimens (χ = 4.32, p = 0.038). The degree of pain relief was significantly inversely correlated to both the degree of WHO graded OM severity (ρ = −0.586; p < 0.001) and the severity of self-reported pain (ρ = −0.375; p < 0.001). Both WHO and OMDQ significantly positively correlated in the clinical setting (p < 0.001). In conclusion, this study highlights the potential advantages of using patient self-reported scales in the local clinical setting. The use of the OMDQ self-reported scales could lead to earlier changes in therapy and may prove useful in HSCT patients.
Keywords: Mucositis, stem cell transplant, WHO oral toxicity scale, OMDQ, pain.